G149 Dose effectiveness of Adenosine in Acute Management of SVT. (27th April 2016) - Fernandes, P; Nathan, M
Abstract : Objective: Supraventricular tachycardia is an abnormally rapid heart rhythm originating above the ventricles. It is one of the most frequently occurring arrhythmia in children with an incidence 1 in 100 to 250. The treatment of choice in acute management is IV adenosine. Adenosine is a Class IC antiarrythmic drug with a very short half life. Current guidelines advice to give the first dose of adenosine as 100mcg/Kg with increment every 2mins. In practice it is very frequently encountered this dose is ineffective. The aim of our study was to determine the effectiveness of the various doses of adenosine in acute management of hemodynamically stable SVTs. Method: This was a retrospective data analyses over a period of 4years from January 2011 to January 2015 in 2 District General Hospitals. Mean age of the patients was 2.5 to 3.5yrs of age. Results: A total of 44 acute episodes were recorded. Out of the 36 patients who received vagal manoeuvres 6 responded. 33 patients in total received IV adenosine. 27% (9/33) received 100mcg/kg as first dose, 33% responded reverting back to sinus, 67% of patients did not respond. 63% (21/33) received 150mcg/kg as first dose, 29% of patients responded, 71% of patients did not respond. 2/33 of the time 1 st dose was >150mcg/kg both responded. 19 patients needed 2 nd dose. 10/17 patients who received 2 nd dose of 150mcg/kg or more responded, 7 patients did not responded and required further doses of >200mcg/kg. 4/33 episodes needed 4 th dose 3 were effective. 1/33 episodes needed 5 th dose of up to 500mcg/kg. Conclusions: Most of the patients in SVT require more than 1 doses of adenosine. The effectiveness of the first dose very much depends on how effectively the medication was administered. Higher first dose of more than 100mcg/kg may have a much higher chance of reverting an SVT if given effectively.